The Frequency of Type I Heterozygous Protein S and Protein C Deficiency in 141 Unrelated Young Patients with Venous Thrombosis - Gladson, C L; Scharrer, I; Hach, V; Beck, K H; Griffin, J H (Thrombosis and Haemostasis, 1988)
The frequency of heterozygous protein C and protein S deficiency, detected by measuring total plasma antigen, in a group (n = 141) of young unrelated patients (<45 years old) with venous thrombotic disease was studied and compared to that of antithrombin III, fibrinogen, and plasminogen deficiencies. Among 91 patients not receiving oral anticoagulants, six had low protein S antigen levels and one had a low protein C antigen level. Among 50 patients receiving oral anticoagulant therapy, abnormally low ratios of protein S or C to other vitamin K-dependent factors were presented by one patient for protein S and five for protein C. Thus, heterozygous Type I protein S deficiency appeared in seven of 141 patients (5%) and heterozygous Type I protein C deficiency in six of 141 patients (4%). Eleven of thirteen deficient patients had recurrent venous thrombosis. In this group of 141 patients, 1% had an identifiable fibrinogen abnormality, 2% a plasminogen abnormality, and 3% an antithrombin III deficiency. Thus, among the known plasma protein deficiencies associated with venous thrombosis, protein S and protein C. deficiencies (9%) emerge as the leading identifiable associated abnormalities.
Keywords: Protein S; Protein C; Thrombosis; Venous thrombosis